Pengembangan Cv. Tumbuh Agridfa Berbasis Digital Di Desa Penengahan, Kecamatan Penengahan, Kabupaten Lampung Selatan - Ayu Firda; Ary Meizari; Amnah (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Community Engagement Program (PKPM) is part of the implementation of the Tri Dharma of Higher Education, focusing on empowering communities through the development of small and medium enterprises. This program was carried out at CV. Tumbuh Agridfa, an agribusiness company located in Penengahan Village, Penengahan Subdistrict, South Lampung Regency. It aimed to address challenges in visual identity, agricultural waste innovation, digital marketing, SOPs, and financial reporting through observation, training, and mentoring. The outcomes include a company logo, corn-cob briquette innovation, a website, employee SOPs, and more accountable financial reports. This program improved the competitiveness, professionalism, and market reach of CV. Tumbuh Agridfa, while serving as a model for other SMEs in adopting digitalization and innovation.